Planejamento e otimização de um método quimiluminescente para determinação de vitamina B12 usando um sistema fluxo-batelada - Moreira, Pablo Nogueira Teles (2008)
The chemiluminescence (CL) of luminol-cobalt(II) reaction has been used in analytical systems for capillary electrophoresis, chromatography, TAS (microTotal Analysis System), etc. Even with the diversity of applications, the steps of this reaction have not been completely elucidated and have been still a subject of research and controversy. Many works reported only to the isolated studies of the influence of each variable in the luminol-cobalt(II) reaction and, as such studies do not consider the interactions among variables, they do not exploit the total performance of this reaction in order to increase the chemiluminescent intensity (ICL). In this context, the use of an experimental design and a ChemiLumimetric Flow-Batch System (CLFBS) is proposed in this work in order to study and to optimize this reaction, aiming at to develop an automatic method to determine vitamin B12 (VB12) in drugs. For optimization purpose, a 24 factorial design was carried out fixing the cobalt concentration at 3.0 g L-1 and varying the concentration of luminol, hydrogen peroxide, sodium hydroxide and the order of mixture of these reagents. Sixteen assays were performed in five replicates, generating a total of eighty experiments. The analysis using normal plot of the experimental design revealed that the luminol concentration and the order of mixture of the reagents are variables more important than the NaOH or H2O2 concentrations to luminol-cobalt(II) reaction. These two parameters were responsible to enhance the chemiluminescent signal in about 80%. Another study was carried out in order to evaluate the CLFBS performance by using the optimized variables which were suggested by the factorial design study. Calibration curves were built by using standard solution of Co(II) and VB12 and the analytical parameters for Co(II) curve were: ICL = -21.39 +1771.37[Co2+] (r2 = 0.9996), LD and LQ = 12.0 ng L-1, RSD = 1.8% (n = 5), analytical sensitivity = 1947.29 W/g L-1; and VB12 curve were: ICL = -186.71 + 12.90 [VB12] (r2 = 0.9999), LD = 14.53 mg L-1 and LQ = 14.70 mg L-1, RSD = 2.1% (n = 4) and analytical sensitivity = 10.76 W/g L-1. The results of the vitamin B12 analysis in drug samples employing the luminol-cobalt(II) reaction and CLFBS were enough satisfactory. Relative errors smaller than 4% were obtained by using curve calibration or standard addition method. The recovery studies yield very good values, which were of 97 to 103%. In addition, a good agreement was obtained when a drug sample was analyzed by the proposed and the reference (HPLC) method. Thus, the automatic chemilumimetric method, which was here developed and optimized, can be considered a promising alternative to quality control of vitamin B12 in drugs.